Influence of non-Saccharomyces yeasts on white dry wines - Alain Poulard; Xenia Pascari; Boris Gaina (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
It was demonstrated a positive action of the non-Saccharomyces yeasts on the organoleptic properties of wines. Also, their participation in fermentation process did not involve an excessive accumulation of volatile acidity or other taste and aroma defects. The involvement of the non-Saccharomyces yeasts in practical oenology that keeps on recent achievements in oenological biotechnologies allow an increase of aromatic intensity (floral, fruitful etc.) in varietal wines and preserve the varietal identity of obtained wines.
Keywords: 330; yeasts; non-Saccharomyces; Saccharomyces cerevisiae; alcoholic fermentation; kinetics of alcoholic fermentation; white dry wines